Batch sorption and fixed-bed elution for Pd recovery using stable amine-functionalized melamine sponge. (20th February 2022) - Yu, Chuande; Wu, Zhaojiang; Wang, Shengye; Zhong, Qilong; Yang, Bo; Xu, Jiajie; Xiao, Ke; Guibal, Eric
Abstract: Sorption-based techniques have been widely studied for metal recovery. Conventionally, sorption and desorption steps are operated in fixed-bed column system under one-pass mode (FO); however, such sorption requires a large volume of solution passing the bed when the feed concentration is low. In this study, highly stable amine-coated alginate melamine (ML/APG) sponge was prepared and applied in a combined process involving sorption under fixed-bed recirculation mode (FR, simulating batch system) and desorption under FO for Pd(II) concentration. The efficiency was evaluated in terms of both recovery of Pd(II) and utilization of the sponge. Results show that ML/APG sponge is stable in 3 M of nitric acid, sodium hydroxide and sodium chloride after shaking at 300 rpm for 72 h with mass loss less than 0.9%. The maximum sorption capacity obtained by Langmuir model for Pd(II) increases from 9.7 mg g −1 to 134.3 mg g −1 after amine functionalization. The sorption equilibrium could be achieved by a less amount of solution and less time when using FR compared to FO. For example, it only needs 0.7 L of Pd(II) solution with a metal concentration of 20 mg L −1 to achieve the maximum sorption capacity under FR, while the required volume is 1.8 L at flow rate of 1 mL min −1 and more than 5 L at 10 mL min −1 under FO. This means that FR improved the rational use of the sorbent and thus increased sorption efficiency. For elution step, FO only required 40 mL to completely desorb Pd(II) from exhausted sponge, while that needed more than 200 mL under FR. The combined process allows both effective sorption and elution. The reusability of ML/APG sponge and Pd(II) recovery from low-concentration solution were studied by combining FR for sorption step and FO for elution step. Results show that the sorption efficiency maintains more than 96% after 100 min of reaction during 10 cycles. The elution performance is stable with a 100% desorption efficiency by passing 50 mL of acidic thiourea solution. The concentration factor (CF, ratio of metal concentration in the eluate over its concentration in the sorption used for sorption), is above or close to 70 for the first 10 mL-sample and much more than 40 for the second 10 mL-sample. Graphical abstract: Image 1 Highlights: ML/APG sponge is highly stable in various aqueous media. Amine functionalization improves Pd(II) sorption by 14 times. Combining FR for sorption and FO for elution improves the concentration factor. Pd(II) is preferentially sorbed compared to coexisting metal ions.